2015
DOI: 10.1364/ol.40.000546
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic nanoshell functionalized etched fiber Bragg gratings for highly sensitive refractive index measurements

Abstract: A novel fiber optical refractive index sensor based on gold nanoshells immobilized on the surface of an etched single-mode fiber including a Bragg grating is demonstrated. The nanoparticle coating induces refractive index dependent waveguide losses, because of the variation of the evanescently guided part of the light. Hence the amplitude of the Bragg reflection is highly sensitive to refractive index changes of the surrounding medium. The nanoshell functionalized fiber optical refractive index sensor works in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Another approach for increasing the FBG sensitivity would be the immobilization of gold nanoparticles, since they induce RI dependent waveguide losses. Thus, the shift and the intensity of Bragg wavelength are SRI-sensitive [ 29 ]. Interestingly, bare FBG fibers without any etching but antibody immobilization at fiber surface have also been recently shown for successful E. coli detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach for increasing the FBG sensitivity would be the immobilization of gold nanoparticles, since they induce RI dependent waveguide losses. Thus, the shift and the intensity of Bragg wavelength are SRI-sensitive [ 29 ]. Interestingly, bare FBG fibers without any etching but antibody immobilization at fiber surface have also been recently shown for successful E. coli detection.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, the sensitivity of the FBG-sensor depends on the cladding thickness, because only part of the guided light propagates as evanescent wave into the cladding [ 25 ]. For removing the fiber cladding, different approaches have been reported in the past, such as side-polishing [ 26 , 27 ] or fiber etching with hydrofluoric acid (HF) [ 28 , 29 ]. Finally, the realized fiber diameter determines the degree of Δ λ B as a result of an altered surrounding refractive index (SRI) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary goal of future development work will be, therefore, to increase the sensitivity and to reduce any disturbing influences while maintaining mechanical stability. Current research has shown that the etch rate of silica glass inside hydrofluoric acid increases significantly through femtosecond laser exposure [22]. Due to a higher pulse energy input, just below the damage threshold, cone cavities form at the focus points of the laser, so that the surrounding medium can penetrate directly into the sensor location and an immediate interaction with the measuring light can be realized.…”
Section: Battery Manufacturing and Surface Cladding Waveguide Bragg Gmentioning
confidence: 99%
“…The OSA is also connected so that both source and detector remain located at the same side of the optical path. For etched FBGs no additional element is required due to the nature of their reflection response [ 100 ] and certain algorithms can be used for increasing the resolution of the measurements [ 101 ]. For the rest of the summarized alternatives, a mirror is deposited on the fiber tip in order to allow back-reflection of the light modes that are sensitive to the external medium [ 102 ].…”
Section: Interrogation Of Plasmonic Fiber-grating (Bio)chemical Sementioning
confidence: 99%